2015
DOI: 10.1038/gim.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of P4HA2 encoding prolyl 4-hydroxylase 2 are associated with nonsyndromic high myopia

Abstract: Conclusion:P4HA2 was identified as a novel causative gene for nonsyndromic high myopia. This study also indicated that the disruption of posttranslational modifications of collagen is an important factor in the pathogenesis of high myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 24 publications
3
54
0
Order By: Relevance
“…Interestingly, HM occurs concomitantly in IRD patients with GRM6 or CACNA1F mutations (32,62). Our findings are consistent with a previous study showing that 23.8% (71/298) of patients with EOHM actually harbor mutations in IRD genes (38).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, HM occurs concomitantly in IRD patients with GRM6 or CACNA1F mutations (32,62). Our findings are consistent with a previous study showing that 23.8% (71/298) of patients with EOHM actually harbor mutations in IRD genes (38).…”
Section: Discussionsupporting
confidence: 82%
“…Population-based epidemiological investigations found that the disease is associated with environmental risk factors, such as a close reading distance and less outdoor activity (8,9). With the advent of nextgeneration sequencing, a few of disease genes have been discovered in recent years (18)(19)(20)(21)(22)(23)(24). Because myopia is dependent on both genetics and lifestyle and preschool children have less exposure to environmental risks, we designed this study using a special cohort with EOHM.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In humans, a deficiency of ascorbate leads to scurvy, 12,13 a disease caused by collagen instability. 14 Moreover, nonsyndromic high myopia (which is a leading cause of blindness 15 ) and certain neurological processes 16 could arise in part from low CP4H activity. The complete loss of CP4H activity is lethal to Caenorhabditis elegans 17,18 and mice.…”
mentioning
confidence: 99%
“…14,15 Further studies analyzing nonpathogenic myopia (MSE < −1.00 D) in highly aggregated families identified genomic regions likely to be harboring high-risk genetic variants. 1620 Although several chromosomal regions have been identified in families with strong linkage evidence for causal variants with a large effect on myopia risk, the specific causal genes and specific risk variants have not been identified.…”
mentioning
confidence: 99%